MoO3/TiO2/Ti3C2Tx nanocomposite based gas sensors for highly sensitive and selective isopropanol detection at room temperature. Issue 15 (14th March 2022) - Yao, Yu; Han, Yutong; Zhou, Ming; Xie, Lili; Zhao, Xueling; Wang, Zifeng; Barsan, Nicolae; Zhu, Zhigang
Abstract : The MoO3 /TiO2 /Ti3 C2 Tx composite was synthesized by a simple one-step hydrothermal method. Due to the formation of more active centers and heterojunctions, the sensor has excellent performance for VOCs and has a unique response to isopropanol. Abstract : Two-dimensional transition metal carbides (MXenes) with outstanding metal conductivity and unique gas sensing characteristics have become a rising star in detecting volatile organic compounds. However, the chemical instability of MXenes, such as easy oxidation in high temperature and humid environments, leads to the reduction of electrical properties, which may limit their use in long-term operation applications. In this work, we introduce MoO3 with many oxygen vacancies through a facile method to improve the conductivity of TiO2 /Ti3 C2 T x, and improve its stability and electrical properties through a ternary heterostructure. We also demonstrate a gas sensor based on the MoO3 /TiO2 /Ti3 C2 T x composite, and the beauty of such sensors is their stability under high oxidation conditions. In addition, due to the formation of more active centers and heterojunctions, the sensor's response to various VOCs at room temperature is 20–40 times higher than that of the pristine MXene sensor. Moreover, it has a unique and better response to isopropanol vapor. This work offers a solution to the industrial application of MXene based gas sensors.